2019
DOI: 10.1093/infdis/jiz641
|View full text |Cite
|
Sign up to set email alerts
|

A Praziquantel Treatment Study of Immune and Transcriptome Profiles inSchistosoma haematobium-Infected Gabonese Schoolchildren

Abstract: Background Although Schistosoma haematobium infection has been reported to be associated with alterations in immune function, in particular immune hyporesponsiveness, there have been only few studies that have used the approach of removing infection by drug treatment to establish this and to understand the underlying molecular mechanisms. Methods Schistosoma haematobium-infected schoolchildren were studied before and after pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Clearance of infection following PZQ administration results in increased effector T cell frequency, increased Schistosome-specific cytokine response and decreased levels of T reg. This contrasts with the immune suppressive profile during infection such as antigen specific hypo-responsiveness, T cell memory pool distortion and increased CD4+CD25+FOXP3+T cell numbers ( 177 ). Consequently, in a randomized trial in Entebbe, Uganda, PZQ treatment significantly, although transiently, improved vaccine response to measles immunization in S. mansoni infected pre-school children ( 169 ).…”
Section: Introductionmentioning
confidence: 97%
“…Clearance of infection following PZQ administration results in increased effector T cell frequency, increased Schistosome-specific cytokine response and decreased levels of T reg. This contrasts with the immune suppressive profile during infection such as antigen specific hypo-responsiveness, T cell memory pool distortion and increased CD4+CD25+FOXP3+T cell numbers ( 177 ). Consequently, in a randomized trial in Entebbe, Uganda, PZQ treatment significantly, although transiently, improved vaccine response to measles immunization in S. mansoni infected pre-school children ( 169 ).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have focused on the Th1 and Th2 cytokines [ 24 , 31 , 32 , 33 ]. In contrast, the behavior of cytokines from the Treg and Breg lymphocyte subsets during infections caused by the main Schistosoma species has not been fully investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of Treg and Breg during chronic infection is associated with suppressed development of pathology [ 19 ] and down-modulated Th1 and Th2 responses [ 20 , 21 ], promoting parasite survival within the host [ 22 , 23 ]. Treatment with the anti-schistosomal drug praziquantel (PZQ) leads to clearance of infection [ 24 ], elevated antigen-specific T-cell proliferation [ 15 ], and cytokine production [ 10 , 16 ]. However, after PZQ treatment, it an increase in effector T-cell frequencies (Th1 and Th2) with increased antigen-specific cytokine production was observed, with a concurrent decrease in the levels of the Treg subpopulation and their secreted specific cytokines [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar experiments have not been performed with NK cells, but lymph node NK cells stimulated by IL-12 shortly after vaccination are believed critical to the subsequent development of antigen-specific Th1 cells (73). Recently, a PBMC transcriptomic study in schoolchildren revealed that infection with S. hematobium is associated with reduced gene signatures for natural killer (NK) cells, DCs, monocytes and T-cell activation (74). There is also a suggestion from an experiment in pigs immunized with one dose of UV-attenuated Schistosoma japonicum, that Granzyme B increase in skin-draining lymph nodes was associated with protection (25).…”
Section: The Impact Of Multiple Vaccinations and Possible Nk Cell Invmentioning
confidence: 99%